DETERMINANTS OF FOREIGN DIRECT INVESTMENT INFLOWS IN THE EUROPEAN UNION (EU) - Gülcü, Yunus (My University, 2024)
This study investigates the institutional factors influencing foreign direct investment within the Eurozone of the European Union (EU) and explores their correlation with economic integration. Attracting foreign direct capital investments is closely related to countries' efforts to make their institutional structures more competitive. Because economic integrations can contribute to economic growth by allowing these investments to increase. For his reason, the study focused on the course of foreign direct capital investments in the Eurozone in the 2002-2022 period and the institutional determinants of these investments were analyzed using the panel data method. The empirical analysis revealed that variables such as foreign direct investment, government effectiveness, political stability, and accountability did not experience any significant shocks. In the short term, a direct causal relationship between foreign direct capital investments and corruption has been found. Nevertheless, in the long term, it has been established that variables such as control of corruption, government effectiveness, political stability, rule of law, accountability, and regulatory quality collectively exhibit a causal relationship with foreign direct capital investments. These findings emphasize the importance of institutional structure for increasing foreign direct capital investments. Enhancements in governmental efforts to combat corruption, enhance governance effectiveness, promote political stability, uphold the rule of law, enhance accountability, and improve regulatory quality can significantly contribute to fostering foreign direct investment. In conclusion, this study provides valuable insights into the determinants of foreign direct investment in the euro area and offers guidance for future policy actions.
Keywords: Panel Data; Foreign Direct Investment; Institutional Quality